Long‐Run Trends in Workers' Beliefs about Their Own Job Security: Evidence from the General Social Survey - Schmidt, Stefanie R. (Journal of Labor Economics, 1999)
In recent years, Federal Reserve Chairman Alan Greenspan, former U.S. Secretary of Labor Robert Reich, and many journalists have argued that workers are more anxious about losing their jobs than they were in the past. I use the 1977‐96 General Social Survey to document trends in workers' beliefs about their own job security. During the 1990s, workers have been more pessimistic about losing their jobs in the next 12 months than workers were during the 1980s. Workers have also been more concerned about suffering future job loss that would have resulted in a decline in earnings or a spell of unemployment.